Early identification and elective inpatient management of high-risk people living with diabetes diagnosed with COVID-19 decreases morbidity and mortality: a quasi-experimental study - Aronson, Tatum (Department of Public Health and Family Medicine, 2023)
Introduction: The Diabetes-COVID-19 relationship is complex, resulting in increased morbidity and mortality. In response to this enhanced vulnerability of people living with diabetes (PLWD) to COVID-19 morbidity and mortality, the Western Cape Department of Health established a telemedicine team (the VECTOR team) that fast tracked at-risk PLWD diagnosed with COVID-19 into the Hospital of Hope (HOH), a temporary intermediate health care facility (ICHF) established as a field hospital to cater for the anticipated overburdening of the acute hospitals in the Cape Metro. This study evaluated the effects of implementing a telemedicine mediated rapid admission process and applying a tertiary hospital practice guideline (the High Risk Diabetes-COVID-19 protocol - HRDCp) for treating high risk PLWD who were electively admitted to a field hospital. Aim: To assess the impact of early admission and application of a clinical practice guideline (HRDCp) developed for use at a specialised tertiary facility for the inpatient care of PLWD who were diagnosed with COVID-19, on clinical outcomes in a generalist run, intermediate healthcare facility. Methods: Using a retrospective quasi-experimental study design applied to the clinical dataset for the HOH, patients admitted prior to the implementation of the clinical protocol (control group) were compared to those admitted via the telemedicine team, who received care using the clinical protocol (experimental group). A total of 183 patients were included in this study. Using secondary data from the hospital clinical dataset, baseline characteristics, inpatient clinical course and clinical outcomes were compared between these two groups. Findings: The key findings showed that the experimental and control groups were similar at baseline for age, gender, renal function and co-morbidity. Glucose control on admission was better in the experimental than in the control group [HbA1C 8.1 vs 9.3% (p=0.013); HGT 10.2 vs 10.7 g/dL (p=0.039)].The experimental group needed less oxygen (p< 0.001), less antibiotics (p< 0.001), and less steroids (p=0.003), while the control group had a higher incidence of acute kidney injury during admission (p=0.046). The median inpatient glucose control was better in the experimental group (8.3 vs 10.0; p=0.006). The two groups had statistically similar clinical outcomes for discharge home (94% vs 89%), escalation in care (2% vs 3%) and inpatient death (4% vs 8%). Ethical considerations: Ethics approval was obtained from the Human Research Council University of Cape Town. (HREC 502/2020) Conclusions: This study demonstrated a novel approach that foregrounds risk of adverse outcomes as criteria for elective admission. Aggressive management had comparably good outcomes versus the usual practice of waiting for severe disease to arise and subsequent emergency admission. While showing noninferiority to usual care in terms of clinical outcomes, it is suggested that significant savings were made in terms of financial costs and emotional distress.